DEVELOPMENT OF SHRINKAGE CALCULAITION FOR MEN'S SHIRT BASE PATTERN MANUFACTURED BY THE GARMENT DYEING METHOD - Sidikjanov, Jafar (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Abstract: Objective. In this article, drawing the basic pattern and method of calculating the shrinkage values ​​for selected cotton fabric to design of a men's shirt produced by the garment dyeing way has been researched, and the basic pattern based on the shrinkage values ​​has been developed. Methods. In order to draw the basic pattern of a men's shirt, M.Müller & Sohn's method was selected. This method offers convenience in constructing the base pattern, as it allows for the use of a few basic body measurements to build the basic pattern of various garments. In this approach, auxiliary measurements are derived using specific ratios of the main measurements, along with certain fixed values. By utilizing this technique, pattern construction becomes faster, requiring fewer body measurements and formulas. As a result, the design processes become more efficient, enhancing overall productivity. Results. In order to design the drawing of the base pattern of the men's shirt, the necessary body measurements were determined according to the typical figure size 176-100-88 and the ease allowances were selected. According to abovementioned method, the base pattern of the shirt was made and a new formula was developed for calculating the values ​​of shrinkage to it. Conclusion. Garment dyeing is extensively utilized in warm climate countries like Uzbekistan for the production of cotton summer casual clothes in menswear. However, a thorough analysis of available sources reveals a lack of sufficient study and development of design principles for clothing production using this method.